Chlorothalonil exposure impacts larval development and adult reproductive performance in Drosophila melanogaster - Darshika M. Dissawa; Ines Boyer; Fleur Ponton (Royal Society Open Science)
Chlorothalonil, a widely used fungicide in agriculture, has raised concerns regarding its impact on non-target species. This study examined the effects of chronic chlorothalonil exposure on larval development and reproductive performance of the vinegar fly, Drosophila melanogaster. Drosophila eggs were reared on a diet supplemented with sublethal concentrations of chlorothalonil (5–120 mg kg−1). Larval pupation was measured as an indicator of survival and growth, while fecundity, ovariole count and body weight served as proxies for female reproductive performance. A ferrozine assay was used to examine mitochondrial mitoferrin activity in males as a reproductive marker related to iron metabolism. Chlorothalonil exposure decreases larval survival, extends developmental duration and reduces fecundity. Even at the lowest tested concentration, chlorothalonil exposure resulted in reduced body weight, ovariole count and egg production compared with non-exposed individuals. Male flies also demonstrated reduced iron levels. These findings underscore that chronic, sublethal chlorothalonil exposure not only induces larval mortality but also adversely affects fecundity in adult insects. Assessing the toxicological effects of agrochemicals on non-target organisms is critical to understanding the broader environmental impacts of these substances. Such insights are vital for developing conservation strategies that safeguard ecosystems and support biodiversity while promoting sustainable agricultural practices.